Dog wars : a Victorian steampunk adventure - Molino, Nicolene Chloe (Rhodes University, Faculty of Humanities, Institute for the Study of English in Africa, 2013)
We're in an alternate universe, circa Dickensian London. Leofric Lieven, a local crime lord, is about to find the past catching up on him. The Romany Carnival has come to town, and a gypsy woman, his former lover and partner in crime, demands from him a favour which will redress his betrayal of years before: he must secure a stolen object and return it to her. But things go horribly wrong when local delivery boy Cards Bennish is kidnapped by Leofric's competitor before he can deliver the goods that will cover Leofric's debt to the gypsy. In this world, humans can shape shift into animals, entirely or only partially, dog fighting is the favourite pastime for high stakes betting, and power belongs to the highest bidder. The gypsy's final bet, for the highest stakes yet, will seal the fates of a number of people, for better or worse
Keywords: Creative writing; Fiction; South Africa; Creative writing (Higher education); Short stories, South African (English) -- 21st century; South African fiction (English) -- 21st century; English language -- Writing